AB0922 Metabolic syndrome is associated with active disease in psoriatic arthritis and may contribute to development of syndesmophytes. (12th June 2018) - Sanci, P.; Kenar, G.; Zengin, B.; Uslu, S.; Koken, A.; Yarkan, H.; Ellidokuz, H.; Can, G.; Birlik, M.; Onen, F.
Abstract : Background: An increased prevalence of metabolic syndrome (MetS) has been reported in psoriatic arthritis (PsA) suggesting an association between the inflammation and MetS. Objectives: The aim of this study is to investigate its relationship with disease activity in patients with PsA. We also evaluated whether an association exists between MetS and axial involvement in PsA. Methods: This study included patients with PsA followed in the Rheumatology outpatient clinic at Dokuz Eylul University. Age-matched patients with Takayasu arteritis (TA), an inflammatory systemic disease, were enrolled as diseased controls. The NCEP-ACT III criteria were used to identify subjects with MetS. Disease activity was assessed in patients with PsA by using several parameters including BASDAI, ASDAS, VAS patients' and physician' global, Tender and Swollen joint assessment (28/68), DAS28, DAPSA, CPDAI and SPARCC Enthesitis Index. ESR and serum CRP levels were measured. BASFI and BASMI were used to evaluate functional status and HAQ, ASQoL and DLQI to evaluate health and PASI to measure the severity of psoriasis. Hand and pelvis X-rays and sacroiliac joint MRIs were performed when indicated. Results: There were 104 PsA patients (63.5% F; mean age: 50.9±13.0 years) who fulfilled the CASPAR criteria and 28 TA patients (89% F, mean age: 46.3±9.1) who fulfilled the ACR 1990 criteria. The prevalence of MetS was found to be considerably higher in PsA patients compared to TA patients (45.2% and 21.4% respectively, p<0.001). In the comparison of PsA patients with and without MetS, no differences were found regarding treatment frequencies of NSAIDs, glucocorticoids, DMARDs and anti-TNFs and also mean glucocorticoid dosages. PsA patients with MetS had higher BASDAI, BASFI, BASMI, VAS, ASqOL, CPDAI, ASDAS and HAQ scores compared to PsA patients without MetS (table 1). More patients with syndesmophytes were found among PsA patients with MetS compared to those without MetS (p=0.027). There were no differences in indexes related predominantly peripheral involvement, such as tender and swollen joint counts, enthesitis score and presence of dactylitis. In multivariable regression analysis, presence of syndesmophytes had no relationship with MetS, but still related with ESR and BASMI. Conclusions: This study demonstrates a higher prevalence of MetS in PsA patients compared to TA. It also suggests that MetS might be associated with high disease activity and more severe disease especially in patients with axial involvement. Disclosure of Interest: None declared